Effects of an in-service training program using the routines-based interview - Boavida, T.; Aguiar, C.; McWilliam, R. A.; Correia, N. (Topics in Early Childhood Special Education, 2016)
The focus of this study is an in-service training program rooted in routines-based early intervention and designed to improve the quality of goals and objectives on individualized plans. Participants were local intervention team members and other professionals who worked closely with each team. This training program involved a small number of trainees per group, providing multiple learning experiences across time and various opportunities for self-assessment and monitoring. We investigated (a) the perceptions of the participants about the strengths and weaknesses of the training program, (b) medium-term outcomes of the training with a comparison group, (c) and variables associated with the quality of goals and objectives. This study involved training more than 200 professionals, and results support the effectiveness of the program in improving the quality of goals and objectives, showing the importance of the routines-based interview in producing that improvement.